EXPLORING STUDENTS’ VOICES ON SNBT ENGLISH LITERACY: A NARRATIVE INQUIRY APPROACH - Darmawan, Iwan; Romadhon, M Galuh Elga; Mustofa, Mutmainnah (University of Kuningan, 2024)
This research study examines the challenges encountered by high school students in Indonesia while acquiring English literacy skills for the National Selection Based on Test (SNBT) examination. The research uses a narrative inquiry methodology to gather qualitative data from two participants who come from diverse backgrounds. The researcher aims to gain a thorough understanding of the participants' experiences, perceptions, and challenges associated with the SNBT examination. Using open-ended questions and probing techniques, the researcher was able to identify recurring themes, patterns, and significant insights. Thematic analysis was employed to identify and analyze the main themes and sub-themes that emerged from the respondents' narratives. The findings of the research indicate that language, psychological, and environmental challenges were identified as the primary obstacles. The findings underscore the significance of catering the varied learning needs of students, including language support and personalized instruction. Moreover, offering explicit guidance on the format and requirements of the SNBT test can better prepare students for success. Additionally, integrating technology, such as online resource and tools, into the language curriculum can enhance engagement and provide valuable learning opportunities. These recommendations aim to empower students by equipping them with the necessary tools and support to navigate the challenges of English literacy acquisition and excel in the SNBT examination.